Microplastic occurrence after conventional and nanofiltration processes at drinking water treatment plants: Preliminary results - Barbier, Jean-Sebastien; Dris, Rachid; Lecarpentier, Caroline; Raymond, Vivien; Delabre, Karine; Thibert, Sylvie; Tassin, Bruno; Gasperi, Johnny (Frontiers in Water, 2022)
Microplastics (MP) have been detected in almost all matrices, including drinking water, and assessing the contamination of drinking water with this type of pollution is of utmost sanitary importance. This study aims to evaluate MP contamination of inlet river water and drinking water at three drinking water treatment plants (DWTP) in the Paris region in France. Each plant performs water treatment processes that are efficient for particulate matter removal such as coagulation-flocculation, sand filtration and granular activated carbon filtration. One of the plants also has a parallel water treatment file that uses microfiltration and nanofiltration processes. This file was investigated in order to assess its efficiency compared to the others. To our knowledge, this study is the first to investigate MP contamination in a DWTP using nanofiltration processes. The drinking water distribution network was also investigated, with samples taken at three network points. MP contamination of sizes 25 - 5000 µm was characterized using micro-Fourier transform infrared (µ-FTIR) mapping. Large volumes were sampled to allow low detection limits. Concentrations ranging from 7.4 to 45.0 MP/L were found in inlet water while concentrations ranging from blank level (0.002 MP/L) to 0.260 MP/L were found in outlet drinking water (overall removal rate above 99%). PE, PP and PET were the main polymers found both at the inlet and outlet, but ratios varied significantly at the outlet. No MP were detected in 4 out of the 6 samples from the nanofiltration file, with the two contaminated samples having lower concentrations than the outlet average. Concentrations in the distribution network were overall higher than at the corresponding DWTP outlet, although a high degree of variation between samples was observed. Our results suggest that membrane processes of microfiltration and nanofiltration are more efficient than typical treatment processes, and also that a MP re-contamination within the distribution network itself might occur.